2012
DOI: 10.1088/0004-637x/755/1/56
|View full text |Cite
|
Sign up to set email alerts
|

Clash: Mass Distribution in and Around Macs J1206.2-0847 From a Full Cluster Lensing Analysis

Abstract: We derive an accurate mass distribution of the galaxy cluster MACS J1206.2-0847 (z = 0.439) from a combined weak-lensing distortion, magnification, and strong-lensing analysis of wide-field Subaru BV R c I c z ′ imaging and our recent 16-band Hubble Space Telescope observations taken as part of the Cluster Lensing And Supernova survey with Hubble (CLASH) program. We find good agreement in the regions of overlap between several weak and strong lensing mass reconstructions using a wide variety of modeling method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
207
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(231 citation statements)
references
References 153 publications
21
207
2
Order By: Relevance
“…model-independent manner, effectively breaking the mass-sheet degeneracy. The WL analysis pipeline is described in Umetsu et al (2012). The image-plane reproduction rms(χ 2 ) is 1.…”
Section: Results and Comparison Of The Two Modelsmentioning
confidence: 99%
“…model-independent manner, effectively breaking the mass-sheet degeneracy. The WL analysis pipeline is described in Umetsu et al (2012). The image-plane reproduction rms(χ 2 ) is 1.…”
Section: Results and Comparison Of The Two Modelsmentioning
confidence: 99%
“…The parameter values are summarised in Table 1. We can compare the results for the scales s c in case of the softened isothermal sphere and r s in case of NFW with Umetsu et al (2012). They obtain s c = 0.000028 ± 0.000006 (12) r s = 0.345 ± 0.050.…”
Section: Comparison With Common Lensing Potentialsmentioning
confidence: 95%
“…The observational input data for the relaxed and massive galaxy cluster MACS J1206, Ebeling et al (2001Ebeling et al ( , 2009 Umetsu et al 2012) investigated here consist of a catalogue of member galaxies ) observed in the context of the CLASH project (Postman et al 2012) as part of a large spectroscopic campaign carried out with the Very Large Telescope (VLT; CLASH-VLT Large Programme; Rosati et al 2014). According to Biviano et al (2013) and Annunziatella et al (2014), the spatial incompleteness of the spectroscopic sample varies with position in the cluster by less than 20%.…”
Section: Data Selection and Preparationmentioning
confidence: 99%
“…Masses were derived with the SaWLens code (Merten et al 2009) that consistently combines weak and strong lensing in a non-parametric fashion on adaptively refined grids. The method was thoroughly tested with realistic lensing scenarios and numerically simulated clusters (Meneghetti et al 2010;Rasia et al 2012), and has been used multiple times for the reconstruction of real galaxy clusters (Merten et al 2009(Merten et al , 2011Umetsu et al 2012;Patel et al 2014). For the CLASH analysis, SaWLens combines constraints from HST strong lensing, HST weak lensing and wide-field groundbased weak lensing (except for CLJ1226+3332 whose mass was reconstructed using HST data only) into a single reconstruction of the cluster's gravitational potential from which it derives the surface-mass density.…”
Section: Clash Lensing Massesmentioning
confidence: 99%